Factors Affecting Repurchase Intention - Novita, Wanda; Toar, Yandri Ardolof (SAFE-Network, 2024)
This research endeavors to scrutinize the determinants influencing consumers' satisfaction for repurchasing intention on the Shopee platform, with customer satisfaction posited as an intermediary variable. Employing a quantitative methodology, data from respondents were collected through a google form survey. The sampling strategy involved convenience sampling, yielding a cohort of 102 participants. Data analysis was executed using a partial least squares structural equation model (PLS-SEM), validated through SmartPls 3.0. The findings indicated that delivery service, brand reputation, and cashback promotions exerted a favorable impact on customer satisfaction, thereby positively influencing repurchase intentions. Moreover, customer satisfaction emerged as a mediating factor in the correlation between service delivery and repurchase intentions, as well as between cashback promotions and repurchase intentions.